IMPLEMENTATION OF ACCOUNTING PRINCIPLES IN MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) - Atang Hermawan (Sean Institute, 2022)
The purpose of this research is to find out the extent to which the application of accounting principles is carried out by MSMEs in Tanjungsari District, to find out the perceptions of MSMEs in Tanjungsari District towards accounting, and the factors that cause low accounting for MSMEs in Tanjungsari, Sumedang Regency. The research was conducted using a qualitative approach. Place of research is determined by using purposive sampling. Sources of data used are primary data and secondary data. Data collection techniques were carried out by observation, interviews, documentation, and data triangulation. The results of the study show that the implementation of accounting principles in MSMEs is still not optimal. Even though basic accounting principles such as recording, classifying and disclosing financial transactions are carried out, there are still deficiencies in the application of these principles. This is influenced by the perception that accounting is complicated, troublesome, and not too important. The perceptions of MSME actors arise due to several factors, including educational background, age, unavailability of workers with accounting skills, while production and marketing are top priorities in business. The efforts to apply accounting principles to MSMEs in Tanjungsari District, Sumedang Regency can be carried out by conducting training and education, using accounting system applications, procuring accounting experts, partnerships with financial institutions and using financial consulting services.